2015
DOI: 10.1002/cmdc.201500179
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical–Halogenated Quinoline Combination Therapy Strategy for the Treatment of Pathogenic Bacteria

Abstract: With the continued rise of drug-resistant bacterial infections coupled with the current discouraging state of the antibiotic pipeline, the need for new antibacterial agents that operate through unique mechanisms compared with conventional antibiotics and work in synergy with other agents is at an all-time high. We have discovered that gallic acid, a plant-derived phytochemical, dramatically potentiates the antibacterial activities of several halogenated quinolines (up to 11,800-fold potentiation against Staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Finally,w ep erformed biofilm eradication assays of all soluble compounds against MSSA andM RSA, with the goal of identifyingp rivileged scaffolds against bacterial biofilms. We identified compounds (e.g.,P -11,0,11a nd T-10,10,10) on par with the best biofilm eradication agents to date; [19,23] however, anti-biofilm activity trended with the MIC values observed. Twop revioush ypotheses had attempted to address biofilm eradication capacity, suggesting that 1) polyamine derivatives might play ar ole in dispersion and eradication, [20] or 2) biofilmeradicating properties of QACs might be related to their electrostatic interaction with extracellularp olymeric substances within the biofilm.…”
supporting
confidence: 37%
See 1 more Smart Citation
“…Finally,w ep erformed biofilm eradication assays of all soluble compounds against MSSA andM RSA, with the goal of identifyingp rivileged scaffolds against bacterial biofilms. We identified compounds (e.g.,P -11,0,11a nd T-10,10,10) on par with the best biofilm eradication agents to date; [19,23] however, anti-biofilm activity trended with the MIC values observed. Twop revioush ypotheses had attempted to address biofilm eradication capacity, suggesting that 1) polyamine derivatives might play ar ole in dispersion and eradication, [20] or 2) biofilmeradicating properties of QACs might be related to their electrostatic interaction with extracellularp olymeric substances within the biofilm.…”
supporting
confidence: 37%
“…It should be noted that at wofold improvement in activity was observed across the entire panel of planktonic bacteria (i.e., 13 vs. 5); this suggests that the increased rigidity did slightly improve biological activity.F urthermore, the biofilm eradication properties of 12 and 14 were quite significant, putting them on par with the best reportedt od ate. [19,23] We next focused on investigating the antimicrobial properties of the C-series, focusing primarily on two specific features. First, the synthesis of ac lass of monoalkylatedQ ACs (e.g.,Cn,0,0) bearing two additional amines hasn ot been significantly explored in our labs.…”
mentioning
confidence: 99%
“…8-hydroxyquinoline (HQ) is a well-studied, privileged structure, with activity against a wide range of cell types (Prachayasittikul, Prachayasittikul, Ruchirawat, & Prachayasittikul, 2013;Song, Xu, Chen, Zhan, & Liu, 2015), including anticancer activity (Barilli et al, 2014;Bhat, Shim, Zhang, Chong, & Liu, 2012;Chang, Chen, Wang, Tzeng, & Chen, 2010;Feng et al, 2015;Li et al, 2016;Moret et al, 2009;Mrozek-Wilczkiewicz et al, 2015;Sosi c et al, 2013;Spaczy nska, Tabak, Malarz, & Musiol, 2014), antifungal activity (Cieslik et al, 2012;Musiol et al, 2006), and antibacterial activity (Warner, Musto, Turesky, & Soloway, 1975). The HQ are active against several bacterial species including Staphylococcus aureus and Staphylococcus epidermidis (Abouelhassan et al, 2014(Abouelhassan et al, , 2015Basak et al, 2016;Garrison et al, 2017;Lam et al, 2014), Enterococcus faecium (Basak et al, 2016;Garrison et al, 2017), Burkholderia pseudomallei (Wangtrakuldee et al, 2013), Neisseria gonorrhoeae, (Lawung et al, 2018), Listeria monocytogenes (Cherdtrakulkiat et al, 2016), and Mycobacterium avium (Hongmanee, Rukseree, Buabut, Somsri, & Palittapongarnpim, 2007;Kos et al, 2015). In addition, activity of the HQ compounds against replicating and nonreplicating Mycobacterium tuberculosis has been demonstrated in medium containing copper and in infected guinea pigs (Ananthan et al, 2009;Darby & Nathan, 2010;Hongmanee et al, 2007;Shah et al, 2016;Tison, 1952;…”
Section: Introductionmentioning
confidence: 99%
“…[19] Broxyquinoline (Brox-Q; Figure 2) has ah ydrogen atom in the 2-position compared to HQ-1,w hich hasamethyl group in the 2-position of the HQ scaffold.This single methyl group difference enhances the antibacteriala ctivity of HQ-1 16-folda gainst staphylococcal pathogens while eliminating antibacterial activity against the Gramnegative pathogen Acinetobacter baumannii 128-fold compared to Brox-Q.I na ddition, we found that HQ-1 is capable of eradicating MRSA biofilms. [18,20] These observationsm otivated us to design multiple synthetic routes to achieve rapid and highly diverse analogues at the 2-position of the HQ scaffold for evaluation in antibacterial and biofilm eradication assays against drug-resistants trains of major human pathogens.…”
Section: Introductionmentioning
confidence: 99%